Exploring the Hidden Curriculum of Global Health - Kelly Christine Anderson; Danyaal Raza; Jane Philpott (Social Medicine Publication Group, 2014)
Universities are experiencing a hurried expansion of global health programs to accommodate interested trainees. A growing body of literature has addressed the practical and ethical considerations for singular global health experiences, and other articles have begun to tackle competencies for building global health curricula. However, standardized approaches to teaching global health are frequently absent, leaving learners to build their knowledge through a variety of avenues: formal coursework, informal reading, conferences, research, mentorship, and electives. The hidden curriculum, described as "processes, pressures and constraints which fall outside...the formal curriculum, and which are often unarticulated or unexplored", has been identified as a powerful force in medical education, affecting impressions, decisions, career paths and morale of trainees. Because global health education is evolving rapidly, is it possible it contains its own uncharted hidden curriculum influencing learners in unknown ways? By investigating the contents of the hidden curricula, trainees have the opportunity to reframe and reconsider how it affects them, whether positively or negatively. But identifying and articulating hidden curricula or shared hidden perceptions is not an easy task. We offer four areas of hidden curriculum as opportunities for exploration.